Loss of ‘Epidermal Melanin Unit’ Integrity in Human Skin During Melanoma-Genesis - Casalou, Cristina; Moreiras, Hugo; Mayatra, Jay M.; Fabre, Aurelie; Tobin, Desmond J. (Frontiers in Oncology, 2022)
Cutaneous melanoma can be a most challenging neoplasm of high lethality, in part due to its extreme heterogeneity and characteristic aggressive and invasive nature. Indeed, its moniker ‘the great masquerader’ reflects that not all melanomas are created equal in terms of their originating cellular contexts, but also that melanoma cells in the malignant tumor can adopt a wide range of different cell states and variable organotropism. In this review, we focus on early phases of melanoma-genesis by discussing how the originating pigment cell of the melanocyte lineage can be influenced to embark on a wide range of tumor fates with distinctive microanatomical pathways. In particular, we assess how cells of the melanocyte lineage can differ by maturation status (stem cell; melanoblast; transiently amplifying cell; differentiated; post-mitotic; terminally-differentiated) as well as by micro-environmental niche (in the stratum basale of the epidermis; within skin appendages like hair follicle, eccrine gland etc). We discuss how the above variable contexts may influence the susceptibility of the epidermal-melanin unit (EMU) to become unstable, which may presage cutaneous melanoma development. We also assess how unique features of follicular-melanin unit(s) (FMUs) can, by contrast, protect melanocytes from melanoma-genesis. Lastly, we postulate how variable melanocyte fates in vitiligo, albinism, psoriasis and alopecia areata may provide new insights into immune-/non immune-mediated outcomes for melanocytes in cutaneous melanin units.